New Methodology Colorimetric-SFI Analysis for the Determination of Doxycycline Hyclate in Pharmaceutical Preparations - Magid, Nawras; Hammood, Mohammad K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Doxycycline is one of the tetracycline-class antibiotics used to treat bacterial and protozoan infections. The development method aimed to determine the Doxycycline hyclate in pharmaceutical drugs using a novel, rapid, and sensitive colorimetric-flow injection approach. The adopted method depended on forming a purplish violet colour complex for the doxycycline hyclate-ammonium chloroaurate reagent in an alkali medium, which a homemade SFI Analyzer measured. Both the physical and chemical variables were analyzed and improved. The calibration plot was linear in the 5-70 μg.mL-1 for the green light source, with a correlation coefficient r=0.9976 using the peak height of green light. The limit of detection was 0.5 μg.mL-1 for dilution of the lowest concentration in the linear area of the calibration plot with RSD% % less than 1 % of μg.mL-1 (n=6) concentration of doxycycline hyclate of the green light source. The technique was effectively used to determine the presence of doxycycline hyclate in pharmaceuticals. The devised approach was tested against the conventional method (ultraviolet (UV) spectrophotometry at 553 nm) and was shown to be more sensitive. Moreover, a t-test was used to contrast "true value" with "practical value". At the 95% confidence level, it was found that the values were not significantly different.